Resveratrol-Loaded Liquid-Crystalline System Inhibits UVB-Induced Skin Inflammation and Oxidative Stress in Mice - Fujimura, Andressa T. [UNESP]; Martinez, Renata M.; Pinho-Ribeiro, Felipe A.; Lopes Dias Da Silva, Amélia M.; Baracat, Marcela M.; Georgetti, Sandra R.; Verri, Waldiceu A.; Chorilli, Marlus [UNESP]; Casagrande, Rubia (American Chemical Society (ACS), 2016)
Evidence shows beneficial effects of resveratrol (RES) on human health. However, its poor aqueous solubility limits therapeutic effectiveness. Thus, the use of nanostructured delivery systems for RES, such as a liquid-crystalline system (LCS), could be viable. The purpose of this study was to develop, characterize, and determine the in vivo effectiveness of a RES-loaded LCS. We studied an LCS containing silicon glycol copolymer, polyether functional siloxane, and the polymeric dispersion carbomer homopolymer type B (C974) in the ratio 20:55:25 with and without RES. Results obtained using polarized light microscopy, small-angle X-ray scattering, and rheology analysis showed that the RES-loaded LCS system presents a lamellar structure and behaves as a non-Newtonian fluid presenting pseudoplastic (the apparent viscosity decreases as the stress increases) and thixotropic (the apparent viscosity decreases with the duration of stress) behaviors. Cytotoxicity studies showed that the formulation components are noncytotoxic. Topical application of a RES-loaded LCS protected hairless mice from UVB-irradiation-induced skin damage by inhibiting edema, neutrophil recruitment, lipid hydroperoxide and superoxide anion production, gp91phox mRNA expression, and oxidative stress. The RES-loaded LCS maintained 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing abilities, catalase activity, reduced glutathione levels, and mRNA expression of glutathione peroxidase 1 and glutathione reductase. The RES-loaded LCS also up-regulated matrix metalloproteinase-9 activity, IL-10 production, and mRNA expression of transcription factor Nrf2 and heme oxygenase-1. Therefore, a RES-loaded LCS is a promising new therapeutic approach to mitigate skin photodamage.